Appropriate teaching model on home visit influencing academic achievement and learning outcomes according to the Higher Education Qualification Framework - Suntiwong, Chanathib (Journal of Public Health Nursing, 2022)
This research is an experimental research. to study and compare learning achievement and learning outcomes according to the framework of qualifications in 6 areas before and after the experiment. The sample consisted of 65 nursing students in the 3rd year of a university in the academic year 2021. Purposive sampling was conducted. Teaching was carried out using a combination of teaching styles in 3 methods: descriptive teaching, demonstration teaching and teaching simulations Data were collected using quizzes and questionnaires. The data were analyzed by using statistics, percentage, mean, standard deviation and paired - sample t-test. The results showed that the students had higher learning achievement after the experiment than before the experiment. It was statistically significant at the .05 level (p = 0.00) and the learning outcomes according to the 6 qualification standard frameworks after the experiment were higher than before the experiment with statistical significance at the .05 level (p = 0.00). Based on the results of this research, the university should choose to use a variety of teaching styles as a framework for teaching nursing teaching by considering Lectures, demonstrations, and simulated teaching for nursing education were chosen as they were suitable formats that could develop nursing skills for students as well.